Exploring The Power Clean - Thomas Huyghe; Brent Goriss; Ernest DeLosAngeles; Stephen P. Bird (International Universities Strength and Conditioning Association, 2021)
The power clean and its variations are prescribed by strength and conditioning coaches as part of the 'big three' to develop "total body strength". This article explores the application of the power clean and its variations to athletic performance and introduces strength and conditioning coaches to teaching progressions, with specific emphasis on developing the correct body positioning required for the power clean. Teaching components are addressed with special reference to taller athletes. It is recommended that strength and conditioning coaches teach the hang clean follow a progression model to decrease movement complexity when advancing athletes to the power clean.